Conceptualising objectification: examining objectification antecedents and effects on outgroup perceptions - Ho, Jack Yong (Nanyang Technological University, 2022)
As attention on representational diversity and identity politics intensify, social outgroups feature increasingly in communication; often in ways that are reductive; in service of extraneous interests, and to the detriment of the featured groups. This phenomenon has been identified as objectification - where human subjects in the media are likened to objects. To the researcher’s knowledge, no theoretical framework or instrument currently exists to facilitate objectification research of a non-sexual nature. This thesis seeks to elucidate the concept of objectification as it applies to social groups through three studies to develop an objectification scale, as well as to understand the effects and antecedents of objectification. Study one (n = 304) analysed extant objectification constructs for the development of an objectification scale. Results showed that objectification can be explained through four factors: commoditisation; superiority over targets; instrumentality; and reduction to physical attributes. The scale developed advances conceptual understanding and provides means to integrate objectification scholarship. Next, to investigate the extent to which objectification can affect attitudes towards outgroups with different degrees of social power, study two was conducted as a between-group experiment (n = 167) with one social outgroup (i.e., immigrants) as a reference point. Following exposure to media stimuli that objectifies immigrants, participants completed a survey on interaction intent, social exclusion, and avoidance towards the social outgroup. These results show differential effects, with lower interaction intent, higher social exclusion, and higher avoidance towards objectified outgroups with less power. Study three examined the extent to which stereotype content influences objectification. Guided by the stereotype content model (i.e., warmth and competence), a between-group experiment (n = 231) was conducted where, following exposure to media excerpts with stereotyped content, participants responses were examined. Competent stereotypes were found to significantly influence objectification while warm stereotypes carry less relative influence on objectification. These findings suggest that the framing of social outgroups as “skilled”, “useful” and “valuable” – frames popularly used in public and organisational communication – may counteract with goals of social integration as objectification towards these very social outgroups intensify. The findings also shed light on the possibility of leveraging warm stereotype frames in tampering objectification towards social outgroups. Overall, by providing clarity on objectification’s factors, explaining how attitudes might be shaped by the power of objectified social outgroups, as well as show the influence of stereotypes in facilitating objectification, this thesis advances conceptual and theoretical understandings of objectification, expands research applications and provides implications for communication scholars and practitioners interested in the framing and representations of social groups in the media.